(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Cognitive development and self-concept formation are two interrelated processes that significantly influence a child’s overall psychological and academic growth. Primary school years represent a critical stage during which children develop thinking abilities alongside an emerging understanding of their identity, competencies, and self-worth.